Investigation of the Effect of Parents' Moral Maturity on Child Raising Styles - EROĞLU, Musa (Journal of Management World, 2025)
Throughout their lives, people live with the moral principles that come from their families. It takes a long time for them to realize this. The attitude of parents towards their children is directly effective in shaping the character traits of the child. In other words, the future of a person directly depends on his/her family. In this respect, the family, with its cognitive, emotional and social effects, is the most influential factor in the development of the child compared to most environmental factors. In this study, the effect of parents' moral maturity on their child-rearing styles is examined. Relational survey model, one of the methods based on quantitative research approaches, was used in the study. The sample of the study consisted of 258 parents reached through convenience sampling method. Mann-Whitney U test, Kruskal-Wallis H test, Spearman Correlation analysis and Regression analysis were used in data analysis. As a result of the analyzes, it was determined that there were statistically significant differences in all sub-dimensions of child rearing attitude except incompatibility according to gender, while there were no statistically significant differences in the moral maturity dimension according to gender. Moral maturity, child rearing attitude and all sub-dimensions differed statistically according to age and educational status. According to monthly income, there are statistically significant differences in moral maturity, child rearing attitude and all sub-dimensions except democratic attitude and equality recognition sub-dimension. There are statistically significant relationships between moral maturity and democratic attitude and recognizing equality, rejection of the role of housewife and strict discipline sub-dimensions. While there are positive relationships between moral maturity and democratic attitude and recognizing equality and strict discipline, there is a negative relationship between moral maturity and rejecting the role of housewife. Moral maturity significantly explains about 23 percent of the variance in the total score of child rearing attitude sub-dimensions.